Establishing a model for rural landscape corridor for tourism route planning (FRGS16-018-0517) - Zakariya, Khalilah; Ibrahim, Putri Haryati; Ibrahim, Illyani; Che Haron, Roziha; Tukiman, Izawati; Abdul Wahab, Nur Amirah; Zulkifli, Nabilah Huda (2019)
The rural landscape is a significant attraction in cultural and regional tourism. The ‘authentic’ imagery of the rural landscape has lured people to travel through long-distance routes across states. Numerous tourism literature found that tourism routes have a positive impact on the rural economy. The landscape and attractions along the routes offer a scenic and cultural experience to the tourists. In Malaysia, the development of resources in the rural areas into tourism products is evolving, such as Homestays, agrotourism and others. However, while various works have been done on rural tourism, there is not yet a research that examines how rural attractions and the rural landscape can be integrated to form a regional tourism route. Consequently, rural attractions are fragmented and disconnected, which leads to a less attractive journey for the tourists when engaging in self-drive tourism and interstate touring. Therefore, it is essential to analyse the features of the rural landscape corridor that can contribute to the identification of potential tourism routes. The aim of this research is to establish a Model of Rural Landscape Corridor (RLC) for tourism route planning in Malaysia to conserve and integrate the physical, cultural and environmental features of the rural landscape with tourism activities. This research examines the significant landscape characters along the Kuala Selangor to Sabak Bernam rural routes and the East Coast coastal route that have potentials as tourism driving route. Based on 500 survey questionnaires among locals and tourists, observation and mapping on site, and conducting semi-structured interviews with tour guides and homestay owners, this study evaluated the significant criteria of rural tourism route. The findings suggest that the intangible criteria are pertinent to support the tangible criteria found along the rural route. The three most significant criteria that are important to tourists as well as locals are the presence of the rural lifestyle, agriculture and rural senses. This research concludes by recommending strategies for the tourism route planning that could increase tourism development opportunities, where the planning of resources and attractions can be better integrated to support infrastructural development of a region, conservation and rejuvenation of cultural and natural resources.